Evaluation of Anti-HB Levels in a Multi-Ethnic Cohort of Health Profession Students - Lorenzo Ippoliti; Andrea Pizzo; Agostino Paolino; Luca Coppeta; Giuseppe Bizzarro; Cristiana Ferrari; Andrea Mazza; Claudia Salvi; Ersilia Buonomo; Fabian Cenko; Andrea Magrini; Antonio Pietroiusti (Vaccines)
Background: Despite the widespread implementation of childhood vaccination programmes, hepatitis B virus (HBV) infection remains an ongoing occupational risk for healthcare students. In multi-ethnic and international university settings, differences in vaccination programmes and immune responses must be considered. This retrospective study aimed to assess the prevalence of protective levels of anti-HBs among medical students at an international university in Rome, exploring associations with demographic and vaccination-related factors. Methods: Data were collected from routine occupational health surveillance conducted in 2023. Anti-HB titres were measured in 507 students, and information on age, sex, country of birth, age at vaccination, and time since the last dose was analysed. Results: Overall, 55.0% of students had antibody levels of at least 10 mIU/mL, indicating serological protection. Higher seroprotection rates were observed among students vaccinated in the first year of life compared to those vaccinated later. A significant decline in antibody titres was also associated with longer intervals since vaccination. Students born outside Europe tended to show lower levels of protection. Conclusions: These results emphasise the importance of screening future healthcare professionals and continuously monitoring antibody titres to help reduce HBV infections.